GAMIFYING SOCIAL INNOVATION: ENTREPRENEURIAL DESIGN THINKING FOR SUSTAINABLE SOCIETIES - Lim, Sofia; Suzuki, Sakura; Brown, Emma; Riatmaja, Dodi Setiawan (Yayasan Adra Karima Hubbi, 2026)
The increasing complexity of social and environmental challenges has exposed the limitations of conventional, top-down innovation models in achieving sustainable societal change. Social innovation therefore requires participatory, adaptive, and engaging approaches capable of mobilizing collective creativity and long-term commitment. This study aims to examine how gamification can be strategically integrated into entrepreneurial design thinking to strengthen social innovation processes for sustainable societies. A qualitative and exploratory research design was employed, drawing on secondary data from peer-reviewed literature, policy reports, and documented social innovation initiatives that apply design thinking and gamified mechanisms. Data were analyzed through thematic interpretation to identify patterns of engagement, collaboration, and learning. The results indicate that gamification functions as a structural enabler rather than a superficial motivational tool, enhancing stakeholder engagement, sustaining participation, and supporting collaborative problem-solving throughout iterative design thinking stages. Gamified design thinking was found to foster experiential learning, shared ownership, and adaptability, which are critical for addressing complex sustainability challenges. The study concludes that effective social innovation depends not only on innovative solutions but also on well-designed participatory processes. Integrating gamification within entrepreneurial design thinking offers a promising framework for aligning innovation practices with sustainability goals across diverse social contexts and long-term societal impact.